Safety and efficacy of 30% hydrogen peroxide in seborrheic keratoses – A prospective and interventional study - Shaik Noushin; Breethiga Velusamy; Mohan Krishna Reddy Thotli; Thirupathi Usha Rani; Angidi Sushrutha; Madine Makarand (Asian Journal of Medical Sciences, 2024)
Background: Seborrheic keratosis (SK) is a skin condition affecting the keratinocytes. Although various treatment options are available, the need for a simpler topical treatment approach is unmet. Hydrogen peroxide (HP) acts by forming free radicals and initiates apoptosis in cells.